2000
DOI: 10.1097/00005537-200004000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Intractable Benign Paroxysmal Positional Vertigo in Patients With Meniere's Disease

Abstract: Our data, in conjunction with that of others, suggest that Meniere's disease may predispose patients to intractable BPPV. Hydropically induced damage to the maculae of the utricle and saccule or partial obstruction of the membranous labyrinth may be possible mechanisms that explain the coexistence of Meniere's disease and BPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
2
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 14 publications
5
81
2
8
Order By: Relevance
“…Almost one third of them were MD (2.8%). The incidence of BPPV associated with MD in this series was 3.2% and it is close to the previous reports [11][12][13][14][15] . Differential diagnosis of peripheral vestibular problems is primarily based on the patient's story.…”
Section: Discussionsupporting
confidence: 90%
“…Almost one third of them were MD (2.8%). The incidence of BPPV associated with MD in this series was 3.2% and it is close to the previous reports [11][12][13][14][15] . Differential diagnosis of peripheral vestibular problems is primarily based on the patient's story.…”
Section: Discussionsupporting
confidence: 90%
“…Failure in treatment or greater number of repositioning maneuvers required for the success of treatment may be owed to many different factors, including cupulolithiasis, atelectasia of vestibular membranous labyrinth and inappropriate repositioning maneuvers. The degeneration of utriculus macula or detachment of otolithic membrane would cause failure in therapeutic maneuver 22 . Aranda-Moreno, Jáuregui-Renaud 23 mentioned the fact that the association of BPPV and other labyrinthic affections may increase the number of required therapeutic maneuvers.…”
Section: Discussionmentioning
confidence: 99%
“…Aranda-Moreno, Jáuregui-Renaud 23 mentioned the fact that the association of BPPV and other labyrinthic affections may increase the number of required therapeutic maneuvers. Gross et al 22 described nine cases of patients with Meniere disease associated with BPPV that did not respond to therapeutic maneuvers. In such cases, repeated distensions of the membranous labyrinth caused by endolymphatic hypertension would cause a collapse of the labyrinth or would facilitate the adhesion of particles, which would prevent the removal from the semicircular canals.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular neuronitis is associated with approximately 15% of the cases 6 and Ménière's disease is present between 0.5% and 31% of BPPV 9,10 . Authors such as Gross 11 , conversely, observed that approximately 5.5% of the patients with Ménière's disease presented typical BPPV of posterior semicircular canal and these cases were of difficult clinical control of positional symptomatology. Ishiyama 12 and Lempert 13 have recently described the association between migraine and cause of BPPV in 5% of the cases, as observed in most of the children in the study by Uneri 7 .…”
Section: Introductionmentioning
confidence: 99%